Tribonacci to Infinity

Let T T be the nonnegative integer sequence defined by T 0 = 0 T 1 = 1 T 2 = 1 T n = T n 1 + T n 2 + T n 3 ( for n 3 ) . \begin{aligned} T_0 &= 0 \\ T_1 &= 1 \\ T_2 &= 1 \\ T_n &= T_{n-1} + T_{n-2} +\ T_{n-3}\ \ (\text{for }n \geq 3). \end{aligned} Also let Q = lim n T n T n 1 . Q = \lim_{n\to\infty}\frac{T_n}{T_{n-1}}. Find the value of Q 3 Q 2 Q . Q^3 - Q^2 - Q.


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Pi Han Goh
Mar 16, 2015

Let's generalize this. For positive integer n 2 n\geq 2 , denote n n -bonacci numbers to be the sequence of numbers that follows the recurrence relation that each term is the sum of the previous n n terms, with initial conditions of a 0 , n = a 1 , n = = a n 1 , n = 0 , a n , n = 1 a_{0,n} = a_{1,n} = \ldots = a_{n-1,n} = 0, a_{n,n} = 1 .

Comparing it to Newton's Identity and letting G n = lim m a m , n a m 1 , n \large \displaystyle G_{n} = \lim_{m \to \infty} \frac {a_{m,n}}{a_{m-1,n}} , we have G n G_n satisfying the equation below

x n x n 1 x n 2 x 1 = 0 x^{n} - x^{n-1} - x^{n-2} - \ldots - x - 1 = 0

In this case, n = 3 n=3 , which we get Q = G 3 Q = G_3 thus

Q 3 Q 2 Q 1 = 0 Q 3 Q 2 Q = 1 Q^3 - Q^2 - Q - 1 = 0 \Rightarrow Q^3 - Q^2 - Q = \boxed{1}

Brock Brown
Mar 28, 2015

Python 2.7:

 1
 2
 3
 4
 5
 6
 7
 8
 9
10
11
12
memo = {0:0.0, 1:1.0, 2:1.0}
def trib(n):
    if n in memo:
        return memo[n]
    memo[n] = trib(n-1)+trib(n-2)+trib(n-3)
    return memo[n]
# build table to reduce recursion
infinity = 1000
for i in xrange(infinity):
    trib(i)
Q = trib(infinity)/trib(infinity-1)
print "Answer:", Q**3-Q**2-Q

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...